Does volumetric measurement serve as an imaging biomarker for tumor aggressiveness of ameloblastomas?. (March 2018) - Safi, Ali-Farid; Kauke, Martin; Timmer, Marco; Grandoch, Andrea; Nickenig, Hans-Joachim; Gültekin, Elif; Büttner, Reinhard; Kreppel, Matthias; Zöller, Joachim
Highlights: Volumetric measurement stratifies tumor aggressiveness better than the size. Radiological signs of aggressiveness are more frequent in large ameloblastomas. We recommend a cutoff volume of 20 cm 3 .